Experimental demonstration of GaN IMPATT diode at X-band. (3rd March 2021) - Kawasaki, Seiya; Ando, Yuto; Deki, Manato; Watanabe, Hirotaka; Tanaka, Atsushi; Nitta, Shugo; Honda, Yoshio; Arai, Manabu; Amano, Hiroshi
Abstract: We report the first experimental demonstration of microwave oscillation in GaN impact ionization avalanche time transit (IMPATT) diodes at the X-band. The device used in this study is a single drift diode with a p + –n simple abrupt junction and vertical mesa termination. The reverse I – V characteristic of the diode shows low leakage current, clear avalanche breakdown, and high avalanche capability, as required for IMPATT operation. Microwave testing is performed in an X-band waveguide circuit with a reduced-height waveguide resonant cavity. Oscillations are observed at 9.52 GHz at a power of ∼56 mW.